The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1007/s00421-021-04728-y
|View full text |Cite
|
Sign up to set email alerts
|

Perception of effort during an isometric contraction is influenced by prior muscle lengthening or shortening

Abstract: Purpose: Following a shortening or lengthening muscle contraction, the torque produced in the isometric steady state is distinctly lower (residual torque depression; rTD) or higher (residual torque enhancement; rTE), respectively, compared to a purely isometric contraction at the same final muscle length and level of activation. This is referred to as the history dependence of force.When matching a given torque level, there is greater muscle activation (electromyography; EMG) following shortening and less acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(71 reference statements)
1
2
0
Order By: Relevance
“…Therefore, as perception of effort is not reduced, muscle afferent feedback cannot be considered as a sensory signal processed by the brain to generate the perception of effort. This result reinforces the potential of using the perception of effort intensity as a psychophysiological index of the motor command [24, 27, 8890], as traditionally performed in the neuroscience, cardiovascular physiology and kinesthesia literatures [24, 25, 27, 91].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, as perception of effort is not reduced, muscle afferent feedback cannot be considered as a sensory signal processed by the brain to generate the perception of effort. This result reinforces the potential of using the perception of effort intensity as a psychophysiological index of the motor command [24, 27, 8890], as traditionally performed in the neuroscience, cardiovascular physiology and kinesthesia literatures [24, 25, 27, 91].…”
Section: Discussionsupporting
confidence: 76%
“…We therefore recommend, similarly to others [14, 29, 133], that researchers and clinicians instruct and familiarize their participants to rate their perception of effort specifically by excluding other exercise-related perception(s) from their sense of effort. This is also crucial for researchers investigating the perception of effort as a psychophysiological marker of the magnitude of the motor command [e.g., 88, 90] and using muscle pain as a psychophysiological marker of feedback from group III-IV muscle afferents [e.g., 136, 137].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as perception of effort is not reduced, muscle afferent feedback cannot be considered as a sensory signal processed by the brain to generate the perception of effort. This result reinforces the potential of using the perception of effort intensity as a psychophysiological index of the motor command [24,27,[88][89][90], as traditionally performed in the neuroscience, cardiovascular physiology and kinesthesia literatures [24,25,27,91].…”
Section: Effort Dissociated Subgroupsupporting
confidence: 77%
“…For example, Zenon et al [121] demonstrated that disrupting the supplementary motor area via continuous theta burst transcranial magnetic stimulation decreases perception of effort. Other studies demonstrated a close relationship between perception of effort and physiological variables known to be strongly influenced by the motor command, such as the respiratory frequency [122] or the electromyographic signal [90].…”
Section: Other (Neuro-)physiological Signals Potentially Processed By...mentioning
confidence: 91%